Peran Etika Bisnis Terhadap Kepercayaan Konsumen - Hasna Lutfi Indriani; Ulviana Agustina; Ulya Triana Dahar; Agustiawan Agustiawan (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2024)
Business ethics is a business approach to conducting operations that covers all aspects of society, business and the public. Business ethics in an organization can influence the values, norms, and behavior of leaders and staff. Consumer trust is the confidence that consumers have in a product, service, or brand. This belief has an important role in influencing consumers' decisions to buy, reuse, and recommend certain products and services. CSR is a business initiative to consider the concerns of many stakeholders, including the environment, society, workers, and customers. The purpose of this research is to find out how important company ethics is in building consumer trust. This research uses a qualitative descriptive analysis method and data is obtained from literature studies, several books, references on the internet, and journals that examine similar research to support research on "The Role of Business Ethics in Building Consumer Trust". This research shows that a company's most morally responsible practices influence customer trust. This study highlights how urgent it is to see how the most morally responsible corporate practices influence customer trust. Sharia marketing strategies have a significant effect on consumer satisfaction and their trust in certain products and services. This research shows that the role of business ethics has a significant influence in building consumer trust.